(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article describes the artistic features of the odes of the national poet of Uzbekistan Erkin Vahidov through the methods of formal-structural, sociological and psychological, comparative-typological analysis. In it, the poet’s traditional and innovative skills are revealed through images. Also, the poet’s odes were scientifically analyzed from the point of view of rhyme, weight, and radif, as well as chronotope . The poet’s ode " Uzbegim " was treated from the chronotopic point of view.